(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Citrullus lanatus (Watermelon) is a commonly consumed fruit whose phytochemical constituents have known advantages, however the seeds of this plant are usually discarded. Hyperlipidaemia is a medical condition characterized by an elevation of any or all lipid profile and/or lipoproteins in the blood. This study aimed to investigate the hematological effects and lipid lowering potentials of methanolic extract of C. lanatus seed (MECLS) in hyperlipidemia-induced male Wistar rats. Total of 40 rats were randomly divided into four groups of ten rats each; Normal control group (NCG), Hyperlipidemic control group (HCG), Hyperlipidemic treated groups (HTG1 and HTG2) which were treated with 800mg/kg and 1600mg/kg body weight of methanolic water melon seed extracts for a period of 7 days respectively. Lipid profiles (TC, TG, LDL and HDL) and Hematological parameters of all the animals in each group were determined. The results showed a decrease in TC, PCV, WBC, RBC, HB and PLT, with a corresponding increase in TG, HDL and LDL following treatment with MECLS to hyperlipidemic wistar rats. Treatment of hyperlipidemia with MECLS improves some lipid factors, but its effects are more visible in reversal of negatively altered haematological parameters resulting from hyperlipidemia.